Literatur Riview: Technological Pedagogical and Content Knowledge (TPACK) dalam Pengajaran Keterampilan Berbahasa Arab - Ana Mualimah; Koderi Koderi; Fachrul Ghazi; Ahmad sodiq (Jurnal Pendidikan Indonesia, 2025)
21st century learning requires teachers to be able to involve communication and collaboration skills as well as the use of information technology in learning that can be arranged in a framework in the form of TPACK. There are 7 components that need to be known in TPACK, namely Technological Knowledge, Pedagogical Knowledge, Content Knowledge, Technological Pedagogical Knowledge, Technological Content Knowledge, Pedagogical Content Knowledge, and Technological Pedagogical Content Knowledge. The purpose of this article is to describe 1) the concept of TPACK, and 2) the implementation of TPACK in learning arabic. The results of this study were 1) TPACK is a combination of three essential elements in learning a technology (technological knowledge) that can be used to facilitate the delivery of teaching materials, pedagogical (pedagogical knowledge) that includes methods and learning model that will be applied, and content (content knowledge) which contains learning materials, where the three elements can be arranged in a learning design. 2) Implementation of TPACK in Learning arabic is to combine all components of TPACK in the learning that will be implemented.